The Effect Of Individual Characteristics, Organizational Commitments And Leadership Profiles On Employee Performance In The Implementation Work From Home (WFH) (Study On Student Employees At Mercu Buana University) - Deden Kurniawan; Indra Sarwono (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
This study analyzed the effect of individual characteristics, organizational commitment and leadership profile on employee performance in implementing Work From Home (WFH). The object of this research was student employees of Mercu Buana. This research is qualitative research with a questionnaire instrument as the survey method. The approach used in this research is Structural Equation Model (SEM) with the Smart-PLS analysis tool. A total of 286 respondents participated in this research. The sample size was determined by the sloven formula and generated a sample of 167 employees. This study proves that individual characteristics positively and significantly affect employee performance with a T-statistic value of (3,845). Organizational commitment has a positive and significant effect on employee performance with a T-statistic value (3.136). The leadership profile positively and significantly affect employee performance with a T- statistic value of(4.095).